TO THE QUESTION OF ENGINEERING EDUCATION MODERNIZATION - Valery A. Prokhorov (Moscow Polytechnic University, 2022)
The article focuses on the topical questions concerning implementing of the two-tier engineering education. The author suggests considerations relating to its fundamentalizationon both levels, participation of employers in skills raising system, and formation of a new version of federal state educational standards.